Euparatettix dandakaranyensis sp. nov. (Tetrigidae: Tetriginae)—a new pygmy grasshopper species from Central India - Gupta, Sunil Kumar (Zootaxa, 2016)
Euparatettix dandakaranyensis Gupta sp. nov. is described from Bastar, Chhattisgarh, India. A brief comparison with the type specimen of Euparatettix sikkimensis (Hancock, 1915) formerly placed within the genus Xistra is given. A key to the species of the genus Euparatettix known from the Indian subcontinent is provided.